북한이탈주민의 건강지식, 건강증진행위 및 건강증진행위에 영향을 주는 요인 - 최명애; 이명선; 최정안; 신기수; Choe, Myoung-Ae; Yi, Myungsun; Choi, Jung-An; Shin, Gisoo (Journal of Korean Academy of Nursing, 2012)
Purpose: The purpose of this study was to identify health knowledge, health promoting behavior and factors influencing health promoting behavior of North Korean defectors in South Korea. Methods: Participants in this study were 410 North Korean defectors, over 20 years of age residing in Seoul. They were recruited by snowball sampling. Data were collected from April to June, 2010. Health knowledge, health promoting behavior, self-efficacy, perceived barriers to health promoting behavior and social support were measured by structured questionnaires, and perceived physical and mental health status were measured by one item with 10-point numeric rating scale. The data were analyzed using t-test, ANOVA, and multiple regression. Results: Health knowledge, health promoting behavior, and perceived barriers to health promoting behavior were moderate while self-efficacy and social support were high. Factors influencing health promoting behavior of the participants were found to be self-efficacy, social support and perceived barrier to health promoting behavior. Conclusion: The results of this study indicate that nursing intervention programs enhancing self-efficacy, social support and reducing perceived barriers to health promoting behavior need to be developed for North Korean defectors in South Korea.